1979
DOI: 10.1111/j.1471-0528.1979.tb10802.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Maternal Serum Alpha‐fetoprotein Levels and Fetomaternal Haemorrhage

Abstract: Summary Spontaneous fetomaternal haemorrhage at 14 to 20 weeks gestation resulted in raised serum alpha‐fetoprotein (AFP) levels in 13 of 150 patients attending a genetic counselling clinic. In all 13 patients, the placenta was anterior or fundal in position. By allowing for a rise in serum AFP levels of 4 μg/l for each fetal cell seen in 30 high power fields (Kleihauer test), a 62·5 per cent reduction in the number of patients selected for amniocentesis because of raised serum AFP levels would have been achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…After amniocentesis, up to 20% of patients have evidence of fetomaternal hemorrhage by the KB test or increases in alpha fetoprotein levels (Hay et al , 1979; Dallaire et al , 1980; MacLennan et al , 1994). Samura and colleagues (2003) measured the amount of cff DNA in maternal circulation after amniocentesis and found that it increased significantly in 79% of post-procedure maternal samples.…”
Section: Introductionmentioning
confidence: 99%
“…After amniocentesis, up to 20% of patients have evidence of fetomaternal hemorrhage by the KB test or increases in alpha fetoprotein levels (Hay et al , 1979; Dallaire et al , 1980; MacLennan et al , 1994). Samura and colleagues (2003) measured the amount of cff DNA in maternal circulation after amniocentesis and found that it increased significantly in 79% of post-procedure maternal samples.…”
Section: Introductionmentioning
confidence: 99%
“…Study of the placenta both macroscopically, microscopically and by ultrasound scan has given some insight into the reasons why maternal serum AFP may be raised in association with a normally formed fetus. Any factor allowing feto‐maternal haemorrhage (i.e., a breakdown in the fetal maternal barrier, spontaneous or induced by CVS or amniocentesis) will cause an elevation of maternal serum AFP and indeed the level of maternal serum AFP provides a sensitive indication of this (Hay et al 1979; Fuhrmann et al 1988). Villous surface area increases throughout gestation in normal pregnancies (Boyd 1984), although the rate of growth decreases from 34 weeks.…”
mentioning
confidence: 99%
“…This hypothesis could and should be tested. An alternative hypothesis to explain the relationship between MSAFP and fetal growth could be based on the observation of spontaneous fetalmaternal hemorrhaging and elevated early mid-trimester maternal serum alpha-fetoprotein, as reported by HAY [11]. We are currently examining this possibility.…”
Section: Discussionmentioning
confidence: 99%